First report of Trypanosoma vivax infection in sheep from Nicaragua - Bonilla, José Luis (2021)
In Central America, outbreaks of trypanosomiasis by Trypanosoma vivax have been recorded only in cattle. This is the first report of an outbreak of trypanosomiasis by T. vivax in 30 Pelibuey sheep (2 to 7 years old, male and female) from Nicaragua, which occurred in 2009. Clinical signs included fever, apathy, pale mucous membranes, weakness, progressive weight loss, and sudden death. Infection by T. vivax was detected in 22 (73.3%) sheep by blood smear analysis and/or PCR. Trypanosomes were morphologically identified in 11 (36.7%) blood smear samples, whereas 17 (85%) of the 20 samples subjected to PCR were positive for T. vivax. Eighteen (81.8%) of the 22 infected sheep presented a packed red cell volume (PCV) lower than 25%. Upon diagnosis, the treated animals were clinically recovered and no parasites could be observed in subsequent examinations. Tabanids were po- tential mechanical vectors of T. vivax in the farm. This is the first report of T. vivax in Nicaragua and for the first time this haemoparasite is recorded in sheep in Central America.